Two new species of Olesicampe Förster (Hymenoptera, Ichneumonidae) with a key to species known from China and Oriental Region - Huang, Rui-Fen; Khalaim, Andrey I.; Sheng, Mao-Ling; Li, Tao (Zootaxa, 2023)
Two new species of Olesicampe Förster, 1869, O. minense Sheng & Khalaim, sp. nov. and O. matouense Sheng & Khalaim, sp. nov., collected from Fujian and Jiangxi provinces of the Oriental part of China, are described and illustrated. A key to the species of Olesicampe known in China and Oriental region is provided.